Analisis Kapasitas Drainase Jalan Piere Tendean Banyuwangi dengan Perangkat Lunak EPA-SWMM - Gibran, Dean Alif; Badriani , Ririn Endah (Jurnal Teknik Sipil, 2024)
Community growth and increasing change over land functions made the road infrastructure unable to hold the runoff water that leads to the drainage. The area for the piere tendean road study became one of the areas in the city of Banyuwangi that have been flooded each year since 2015. The main factor that causes bad drainage lines is too narrow channels, the amount of garbage that covers the lines, and the high rainfall rates in the region. An analysis of the capacity of the channel was needed to see if the drainage line was still able to accommodate the runoff of water by using the 25-year for simulation flooding that ran into the drainage. Software environmental protection agency-storm water management model (EPA-SWMM) is one of the modeling applications that it was designed to reveal flood capacity levels in drainage lines. The research was to identify the flooding of the study area with the EPA-SWMM software at Piere Tendean road. The modeling SWMM was performed with the purpose of simulating runoff discharge of water at 2, 5, 10, and 25 years of age. On the 2 years there were 14 points of flooding. On the 5-year by 3 to flood, the 10 and 25 years increased by 1 to flood. Re-planning with a clogged normalization of the conduit, replacing new dimensions and adding outfall with a 25-year remodel could address the flood on piere tendean road as already done. Ecological drainage along with channel maintenance can minimize floods and standing water in piere tendean road.